Variations of the ulnar nerve within the ulnar tunnel and palm in a select South African population - Lutho Daza; Julia Fernandes; Geney Gunston; Jeshika Luckrajh-Williams (Translational Research in Anatomy)
Background: Ulnar tunnel syndrome (UTS) is a rare peripheral neuropathy associated with the entrapment of the distal portion of the ulnar nerve (UN) in its course through the fibro-osseous ulnar tunnel (eponymously known as Guyon's canal) at the wrist. The UN within the ulnar tunnel is prone to injury or compression resulting in an UTS. Therefore, it is of clinical importance to know the anatomical variations in the branching pattern of the UN within the ulnar tunnel. UTS is characterised by sensory deficits and muscular weakness, impaired sensation of the volar fingertips, and weakness in grasping with intrinsic hand muscles. This study aimed to examine the anatomical variations of the UN in the palm of the hand within a select South African cadaveric population. Methods: The variations in the branching patterns of the UN were examined in 81 cadavers (n = 162) and described according to the classification system of Murata et al. (2004) [10]. Communicating branches were classified according to their description in previous literature. The length of the ulnar tunnel was measured from the level of the pisiform bone to the level of the hook of hamate. Results: The branching pattern was found as Type 1 (52.9 %), Type 2 (34 %), Type 3 (2.7), Type 4 (6.5 %), Type 5 (3.9 %). Berrettini, Riche-Cannieu and Kaplan anastomoses were found in 51.6 %, 2 % and 3.3 % of specimens, respectively. Conclusion: It is important for surgeons to be aware of these anatomical variations as they may lead to misdiagnosis and complications during surgical procedures during the treatment of UTS.